Novel Quantitative Metrics for Foveal Hypoplasia Derived from Optical Coherence Tomography Angiography Using AngioTool - Charlotte Egbring; Sarah Kleemann; Nicole Eter; Jens Julian Storp (Journal of Clinical Medicine, 2026)
Background/Objectives: This monocentric case–control study prospectively recruited patients with foveal hypoplasia (FH) and compared them with retrospectively selected age- and sex-matched healthy controls. It is the first study to employ AngioTool software to quantitatively assess retinal microvascular alterations in FH using Optical Coherence Tomography Angiography (OCT-A). Methods: In total, 19 patients with FH and 19 age- and sex-matched healthy controls were included at Münster University Hospital, Germany, and underwent OCT-A imaging of the macula. The 3 × 3 mm2 angiograms of the superficial (SCP) and deep capillary plexus (DCP) were examined using AngioTool software. Quantified parameters included flow density (FD), number of junctions, total and average vessel length, number of endpoints, and lacunarity. Results: A total of 62 eyes from 38 participants were included in the analysis. Compared with controls, eyes with FH demonstrated significantly lower FD, fewer junctions, shorter total vessel length, and a greater number of endpoints in both SCP and DCP. These differences showed small-to-large effect sizes, depending on the parameter and plexus. Average vessel length remained significantly decreased in the SCP but not the DCP. The difference in SCP lacunarity did not remain significant after adjustment for multiple comparisons. In the exploratory subgroup analysis, there were no significant differences between mild and severe FH in either the SCP or the DCP after correction for multiple testing. Conclusions: FH is associated with alterations of retinal microvasculature involving both the SCP and DCP. These findings are consistent with altered retinal vascular development in FH. OCT-A may provide useful quantitative information for the characterization of FH, although the clinical and prognostic relevance of these vascular parameters remains to be established.